2012
DOI: 10.1136/gutjnl-2011-300926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azithromycin on acid reflux, hiatus hernia and proximal acid pocket in the postprandial period

Abstract: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=1970 NTR1970.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 40 publications
0
36
0
6
Order By: Relevance
“…In patients with a small hiatus hernia, azithromycin reduced hernia size and increased the amount of time it was in the reduced state. Acid refl ux was also reduced in these patients (38 % to 17 % ) while the total number of refl ux events was unchanged; no eff ects were observed in patients with large hiatus hernia ( 47 ). Th e gammaaminobutyric acid agonist, baclofen, has also been shown to significantly reduce the extent of the acid pocket in healthy volunteers.…”
Section: Therapeutic Agents and The Acid Pocketmentioning
confidence: 82%
See 1 more Smart Citation
“…In patients with a small hiatus hernia, azithromycin reduced hernia size and increased the amount of time it was in the reduced state. Acid refl ux was also reduced in these patients (38 % to 17 % ) while the total number of refl ux events was unchanged; no eff ects were observed in patients with large hiatus hernia ( 47 ). Th e gammaaminobutyric acid agonist, baclofen, has also been shown to significantly reduce the extent of the acid pocket in healthy volunteers.…”
Section: Therapeutic Agents and The Acid Pocketmentioning
confidence: 82%
“…Boecxstaens et al ( 32 ) demonstrated that the administration of the promotility drug erythromycin suppressed the acid pocket, while sumatriptan (a gastric relaxant) had an opposite eff ect. Similarly, Rohof et al ( 47 ) have shown that the prokinetic agent azithromycin can displace the acid pocket to a more distal location ( Figure 4 ). In patients with a small hiatus hernia, azithromycin reduced hernia size and increased the amount of time it was in the reduced state.…”
Section: Therapeutic Agents and The Acid Pocketmentioning
confidence: 99%
“…Vocal training involves changing from thoracic to abdominal breathing and would not strengthen the CD. The acid pocket position is important in the pathogenesis of GERD and can be changed pharmacologically (24). Would vocal training displace the acid pocket distally?…”
Section: Discussionmentioning
confidence: 99%
“…22 Macrolides improve gastric emptying and reduce gastroesophageal reflux, 23,24 and it is tempting to speculate that these effects contribute to a reduction in COPD exacerbations.…”
mentioning
confidence: 99%